The utility of P53 immunohistochemistry in the diagnosis of Barrett's oesophagus with indefinite for dysplasia. Issue 7 (20th May 2022) - Januszewicz, Wladyslaw; Pilonis, Nastazja D; Sawas, Tarek; Phillips, Richard; O'Donovan, Maria; Miremadi, Ahmad; Malhotra, Shalini; Tripathi, Monika; Blasko, Adrienn; Katzka, David A; Fitzgerald, Rebecca C; di Pietro, Massimiliano
Abstract : Aims: Barrett's oesophagus with indefinite for dysplasia (BE‐IND) is a subjective diagnosis with a low interobserver agreement (IOA) among pathologists and uncertain clinical implications. This study aimed to assess the utility of p53 immunohistochemistry (p53‐IHC) in assessing BE‐IND specimens. Methods and results: Archive endoscopic biopsies with a BE‐IND diagnosis from two academic centres were analysed. First, haematoxylin and eosin‐stained slides (H&E) were reviewed by four expert gastrointestinal (GI) pathologists allocated into two groups (A and B). After a washout period of at least 8 weeks, H&E slides were reassessed side‐to‐side with p53‐IHC available. We compared the rate of changed diagnosis and the IOA for all BE grades before and after p53‐IHC. We included 216 BE‐IND specimens from 185 patients, 44.0 and 32.9% of which were confirmed after H&E slide revision by groups A and B, respectively. More than half the cases were reclassified to a non‐dysplastic BE (NDBE), while 5.6% of cases in group A and 7.4% in group B were reclassified to definite dysplasia. The IOA for NDBE, BE‐IND, low‐grade dysplasia (LGD) and high‐grade dysplasia (HGD)/intramucosal cancer (IMC) was 0.31, 0.21, −0.03 and −0.02, respectively. Use of p53‐IHC led to a >40% reduction in BE‐IND diagnoses ( P  < 0.001) and increased IOA for all BE grades [κ = 0.46 (NDBE), 0.26 (BE‐IND), 0.49 (LGD), 0.35 (HGD/IMC)]. An aberrant p53‐IHC pattern significantly increased the likelihood of reclassifying BE‐IND to definite dysplasia (odds ratio = 44.3, 95% confidence interval = 18.8–113.0). Conclusion: P53‐IHC reduces the rate of BE‐IND diagnoses and improves the IOA among pathologists when reporting BE with equivocal epithelial changes. Abstract :